EFFECT OF COMPETENCE, WORK ENVIRONMENT AND CAREER DEVELOPMENT EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION AT PT. SGI GRAHA PROPERTAMA BATAM CITY - Friska Sihombing, Elisabet; Sumiyati, Sumiyati; Satriawan, Bambang; Catrayasa, I Wayan (CV. Radja Publika, 2022)
This research was conducted with the aim of analyzing how the direct and indirect influences of competence, work environment, career development variables on employee performance are mediated by employee job satisfaction. As for the sample of this research are employees of PT. SGI Graha Propertama in Batam City. Questionnaires were distributed to 119 respondents using the Non-Probability Sampling technique. To analyze the research data using multiple regression analysis techniques using SmartPLS Software. Based on the results of the study it can be concluded that the variable, job satisfaction has no significant effect on performance at a significance level of > 0.05. While competence, work environment and career development have a direct and significant effect on performance with alpha <0.05. The results of the study show that competence has no significant effect on job satisfaction with a significance > 0.05. While career development variables, work environment have a significant direct effect on job satisfaction with a significance level <0.05. The results of the indirect effect show that the competency variable on employee performance through work motivation is not significant > 0.05. The indirect effect of work environment and career development variables on employee performance through work motivation is significant <0.05. The coefficient of determination R Square competence, work environment, career development and job satisfaction on employee performance is 64.1% and competence, work environment, career development on job satisfaction is 71.5% competency has no significant effect on job satisfaction with a significance > 0.05. While career development variables, work environment have a significant direct effect on job satisfaction with a significance level <0.05. The results of the indirect effect show that the competency variable on employee performance through work motivation is not significant > 0.05. The indirect effect of work environment and career development variables on employee performance through work motivation is significant <0.05. The coefficient of determination R Square competence, work environment, career development and job satisfaction on employee performance is 64.1% and competence, work environment, career development on job satisfaction is 71.5% competency has no significant effect on job satisfaction with a significance > 0.05. While career development variables, work environment have a significant direct effect on job satisfaction with a significance level <0.05. The results of the indirect effect show that the competency variable on employee performance through work motivation is not significant > 0.05. The indirect effect of work environment and career development variables on employee performance through work motivation is significant <0.05. The coefficient of determination R Square competence, work environment, career development and job satisfaction on employee performance is 64.1% and competence, work environment, career development on job satisfaction is 71.5% work environment has a significant direct effect on job satisfaction with a significance level <0.05.